Psychopathy and Aggression: The Role of Emotion Dysregulation - Garofalo, Carlo (Journal of interpersonal violence, 2021)
The importance of psychopathy in the forensic and criminal justice domains is largely due to its robust associations with aggression and violent behavior. Hence, investigators have increasingly been interested in elucidating potential mechanisms linking psychopathy and aggression. Recent research highlighted previously overlooked associations between psychopathy and difficulties in emotion regulation, the process responsible for monitoring, evaluating, and managing one’s emotional experience, as well as for guiding behavior under intense emotional arousal. Yet, it remains unclear whether emotion dysregulation may be helpful to explain well-documented associations between psychopathy and aggression. The present study examined whether emotion dysregulation mediated associations (i.e., explained a significant portion of the shared variance) between psychopathy and aggression across community (N = 521) and offender (N = 268) samples. Participants completed self-report measures of psychopathy, emotion dysregulation, trait aggressiveness (i.e., anger, hostility, physical and verbal aggression), as well as reactive and proactive aggression. Across both samples, psychopathy had significant indirect effect on all indices of aggression through emotion dysregulation, with the exception of verbal aggression. These findings support the relevance of emotion regulation for the construct of psychopathy and its maladaptive correlates and highlight the potential relevance of focusing on emotion regulation as a possible target for interventions aimed at reducing aggression among individuals with psychopathic traits.